FIGURE 18 in Bivalves from the latest Jurassic-earliest Cretaceous hydrocarbon seep carbonates from central Spitsbergen, Svalbard - Hryniewicz, Krzysztof; Little, Crispin T.S.; Nakrem, Hans Arne (Zenodo, 2014)
FIGURE 18. Measurements of Pseudotrapezium aff. groenlandicum Spath, 1936 (in mm). (A) Height to length, (B) Width to length, (C) Width to height, (D) Length of the posterior to total length. : Published as part of Hryniewicz, Krzysztof, Little, Crispin T.S. & Nakrem, Hans Arne, 2014, Bivalves from the latest Jurassic-earliest Cretaceous hydrocarbon seep carbonates from central Spitsbergen, Svalbard, pp. 1-66 in Zootaxa 3859 (1) on page 43, DOI: 10.11646/zootaxa.3859.1.1, http://zenodo.org/record/4930112